Overview of Glycometabolism of Lactic Acid Bacteria During Freeze-Drying: Changes, Influencing Factors, and Application Strategies - Tchouli Noufeu; Yueqin Li; Ndeye Fatou Toure; Hui Yao; Xiaoqun Zeng; Qiwei Du; Daodong Pan (Foods)
Lactic acid bacteria (LAB) play a vital role in food fermentation and probiotics microeconomics. Freeze-drying (FD) is a commonly used method for preserving LAB powder to extend its shelf life. However, FD induces thermal, osmotic, and mechanical stresses that can impact the glycometabolism of LAB, which is the process of converting carbohydrates into energy. This review explores the effect of FD on glycometabolism, factors influencing glycometabolism, and feasible strategies in the FD process of LAB. During the three stages of FD, freezing, primary drying or sublimation, and second drying, the glycolytic activity of LAB is disrupted in the freezing stage; further, the function of glycolytic enzymes such as hexokinase, phosphofructokinase, and pyruvate kinase is hindered, and adenosine triphosphate (ATP) production drops significantly in the sublimation stage; these enzyme activities and ATP production nearly cease and exopolysaccharide (EPS) synthesis alters during the secondary drying stage. Factors such as strain variations, pretreatment techniques, growth medium components, FD parameters, and water activity influence these changes. To counteract the effects of FD on LAB glycometabolism, strategies like cryoprotectants, encapsulation, and genetic engineering can help preserve their glycometabolic activity. These methods protect LAB from harsh FD conditions, safeguarding glycolytic flux and enzymatic processes involved in carbohydrate metabolism. A deeper understanding of these glycometabolic changes is essential for optimizing FD processes and enhancing the use of LAB in food, medicine, and biotechnology, ultimately improving their performance upon rehydration.